Pengaruh Pelatihan, Motivasi dan Kompetensi terhadap Kinerja (Pemanfaatan Artificial Intelligence dalam Systematic Literature Review Manajemen Sumber Daya Manusia) - Netaniel Giovanni; Hapzi Ali (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The Influence of Training, Motivation, and Competency on Employee Performance is a scientific article on literature studies within the scope of HRM. The purpose of this article is to build a hypothesis of influence between variables that will be used in further research. Research objects based on online libraries such as Google Scholar, Mendeley, and other academic online media. The research method uses a systematic literature review with artificial intelligence (AI) to obtain related research sourced from e-books and open access journals. The analysis uses qualitative descriptive analysis. The results of this article: 1) Training influences Employee Performance; 2) Motivation influences Employee Performance; and 3) Competency influences Employee Performance.